Engineered Stem Cell-Derived Exosomes for Precision Regenerative Medicine: Molecular Targeting, Cargo Optimization, and Therapeutic Applications - Ghea Farmaning Thias Putri; Dwi Widyawati; Firda Asma'ul Husna; Rifdah Hanifah; Nabila Aulia Tsaqifah (International Journal of Cell and Biomedical Science, 2026)
Regenerative medicine has increasingly transitioned from cell-based therapies to cell-free approaches due to the constraints of stem cell transplantation, such as limited engraftment efficiency, immunogenicity, tumorigenic potential, and difficulties in clinical standards. Among novel cell-free methodologies, stem cell-derived exosomes have garnered considerable interest as nanoscale extracellular vesicles that facilitate tissue repair via paracrine signaling. Recent advancements in molecular biology and bioengineering have facilitated the creation of modified exosomes, permitting precise alterations of surface molecules and bioactive cargo to improve therapeutic specificity and efficacy. This narrative review encapsulates current advancements in synthetic stem cell-derived exosomes for precision regenerative medicine, emphasizing molecular targeting techniques, therapeutic cargo optimization, and applicability across various disease types. Literature pertinent to the years 2020 to 2025 was sourced from PubMed, Scopus, and ScienceDirect and subjected to qualitative analysis. The results demonstrate that modified exosomes can efficiently regulate critical biological pathways associated with apoptosis, inflammation, angiogenesis, and tissue regeneration. Improved targeting specificity increases tissue accumulation and therapeutic efficacy, while tailored cargo allows for precise modulation of molecular signaling in damaged microenvironments. Despite encouraging preclinical results, challenges related to production standardization, cargo uniformity, dosage optimization, and long-term safety hinder clinical translation. However, ongoing advancements in bioengineering, nanotechnology, and regulatory structures position modified exosomes as strong contenders for the development of next-generation regenerative therapeutics. Engineered stem cell-derived exosomes are a versatile and unique platform with considerable promise to connect molecular mechanisms and clinical applications in precision regenerative medicine.